Woman Survival in Chinese Feudal Patrilineal Society: An Analysis of Song Lian's Destiny in Qi Qie Chenqun By Su Tong - Xuc Lin (Lingua Cultura, 2009)
Article depicted woman’s difficulties in maintaining her life as well as her aggressiveness in the patrilineal society in Chinese feudal time. Article analyzed Song Lian’s bad fate. She was the main character of qi qie chenqun novel, written by Su Tong. Article analysis consisted of three parts. The first part described Song Lian’s background of life and her becoming a mistress. The second part indicated Song Lian’s attacking behavior to other woman because of defending her life. His third part analyzed some causes that made Song Lian did not survive in life. It can be concluded that the fact, Song Lian is able to be survive but she decides to be a mistress caused by both personal and o social reasons. Song Lian’s attacking other woman is caused by her anger representing her unsuccessful life. Principally, Song Lian’s failure in the feudal life is caused by her unsuccessful in becoming a respected woman. If she had been a respected woman, she would have also competed with other women in achieving a better life.